Decorin Binding by DbpA and B of Borrelia garinii, Borrelia afzelii, and Borrelia burgdorferi Sensu Stricto - Salo, Jemiina (Oxford University Press, 2011)
Background. Decorin adherence is crucial in the pathogenesis of Lyme borreliosis. Decorin-binding proteins (Dbp) A and B are the adhesins that mediate this interaction. DbpA and B of Borrelia garinii, Borrelia afzelii, and Borrelia burgdorferi sensu stricto (ss) differ in their amino acid sequence, but little attention has been paid to the potential difference in their decorin binding. Methods. We expressed recombinant DbpA and DbpB of B. garinii, B. afzelii, and B. burgdorferi ss and studied their binding to decorin. We also generated recombinant Borrelia strains to study the role of DbpA and DbpB in the adhesion of live spirochetes to decorin and decorin-expressing cells. Results. Recombinant DbpA of B. garinii and DbpB of B. garinii and B. burgdorferi ss showed strong binding to decorin, whereas DbpA of B. burgdorferi ss and both DbpA and DbpB of B. afzelii exhibited no or only minor binding activity. DbpA and DbpB of B. garinii and B. burgdorferi ss also supported the adhesion of whole spirochetes to decorin and decorin-expressing cells, whereas DbpA and DbpB of B. afzelii did not exhibit this activity. Conclusions. Dbp A and B of B. garinii and B. burgdorferi ss mediate the interaction between the spirochete and decorin, whereas the same adhesins of B. afzelii show only negligible activity.